The use of nutrition label on food purchasing decision among university students in Kuantan, Malaysia - Hazali, Norazlanshah; I, Muhammad; MD, Hasmira; M, Mashita; MR, Norfazilah; MF, Fazlyla Nadya (School of Health Sciences, Universiti Sains Malaysia, 2013)
Nutrition label provides nutrition status of the pre-packaged foods and is very useful for people when making decision for healthy foods. However, there is a lack of awareness among Malaysians regarding the use of nutrition label when purchasing foods. Hence, a cross sectional study among tertiary students (IIUM) was conducted. The aim of this study was to determine the relationship between gender, attitude and knowledge of the tertiary students with the use of nutrition labeling. Assessment s were done by distributing 25-item questionnaires composed of pair-wise, open-ended and 5-item Likert scale questions to the subjects. The prevalence of level of nutrition knowledge and attitudes were determined. Our analysis showed that 95 students(57.6%) were moderately making use of the nutrition label. There was no significant difference between gender and the use of nutrition label on food purchasing decision among these students. There was also no association between knowledge and the use of nutrition label on food purchasing decision among them. However, there was significant association between attitude and the use of nutrition label on food purchasing decision among the students(p= 0.001, r= 17.842). Our results show that attitude is the key factor in regards with the use of nutrition label while gender and knowledge has no effect on the use of nutrition label on food purchasing